Family functionality, emotional intelligence and adherence to the Mediterranean diet in elementary education students. An explanatory model - Melguizo-Ibáñez, Eduardo; García-Pérez, Laura; Ubago-Jiménez, José Luis; Alonso-Vargas, José Manuel; Sanz-Martín, Daniel; González-Valero, Gabriel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Currently, the family environment is conceived as a fundamental element for the adequate development of adolescents, which is why the present research has the objectives of developing an explanatory model of the incidence of family functionality and emotional intelligence on adherence to the Mediterranean diet in adolescents (b) to contrast the structural model by means of a multigroup analysis according to the degree of adherence to this dietary pattern. For this purpose, a descriptive cross-sectional study was carried out using the KIDMED, APGAR and TMMS-24 questionnaires. Finally, the results show that optimal adherence to the Mediterranean diet is positively related to family functionality, while low adherence to this dietary pattern is negatively related.